Dietary restriction transforms the mammalian protein persulfidome in a tissue-specific and cystathionine γ-lyase-dependent manner - Nazmin Bithi (Nature Portfolio, 2021)
Dietary restriction (DR) can increase protein persulfidation but the tissue specificity of this process is not well understood. Here, the authors compare organ-specific protein persulfidomes in young and aged mice under DR, and show that DR-dependent persulfidome changes depend on cystathionine γ-lyase.